A beginner's guide to New Testament studies: understanding key debates - Gupta, Nijay K. (Baker Academic, a division of Baker Publishing Group, 2020)
The synoptic problem -- The historical Jesus -- The Fourth Gospel and history -- Jesus and Paul -- Paul's theological perspective -- Paul and the Jewish law -- Interpreting the Book of revelation -- Pseudonymity and the New Testament letters -- The New Testament and the Roman Empire -- Women in leadership in the New Testament -- Justification by faith and judgment according to works -- The Old Testament in the New Testament -- The application and use of scripture.